Experimentation and optimization of HDPE pipe electro fusion and butt fusion welding processes. (2020) - Pathak, Saurabh; Pradhan, Sharad K.
Abstract: Recently, pipe welding has been widely applied in the pipe fitting operations. There are many types of pipe welding facilities available. In this research work, experimental investigations related to Electro fusion and Butt fusion welding of HDPE pipe and optimization of different welding process parameters are performed. In electro-fusion welding a fitting device is used for joining of two pipes namely called 'fusion coupler'. Fusion coupler has a copper coil which is wounded in inner surface of coupler. Two pipes are fitted in the coupler and the current is applied in the coil with the help of kitrik pin which has provided in the coupler to generate heat and finally to create the weld. In butt-fusion welding for joining of two pipes, the welded joint is produced with the help of heated plate. After performing the welding, the joints are tested for tensile strength using universal testing machine. Two performance parameters viz. temperature and tensile strength and three process parameters viz. Starting Welding voltage, Specific fusion time and Cooling time for Electro fusion welding and Heating plate temperature, Drag pressure, Welding pressure for Butt fusion welding of HDPE pipes (82 mm inner diameter and 8 mm wall thickness) are optimized using Grey relational analysis optimization technique. The optimized parameters for electro fusion welding of these pipes are welding voltage, specific fusion time, cooling time and optimized parameters for Butt welding are heating plate temperature, drag pressure, welding pressure.